Spectrophotometric Determination of Nebivolol Hydrochloride in Bulk and Pharmaceutical Formulations - Murali, D.; Neeharika, T.; Rambabu, C. (Asian Journal of Chemistry, 2013)
Two simple, rapid, sensitive and accurate spectrophotometric methods have been developed and validated for the assay of nebivolol hydrochloride in pure and pharmaceutical formulations. These methods (A and B) were based on nucleophilic substitution and co-ordination complex formation of nebivolol hydrochloride by 1,2-naphtha quinone-4-sulphonate in alkaline media and cobalt thiocyanate with the maximum absorption at 460 and 630 nm respectively. Reaction conditions were optimized to obtain the maximum colour intensity. Absorbance was found to increase linearly with increase in concentration of nebivolol hydrochloride, which was corroborated by the correlation coefficient values 0.9986 and 0.9984 respectively. The developed methods were validated with respect to linearity, accuracy (recovery), precision, Sandell's sensitivity, molar extinction coefficient and specificity. The system obeyed Beer's law in the range of 10-60 μg/mL and 8-20 μg/mL for nebivolol hydrochloride. Various analytical parameters have been evaluated and the results have been validated by statistical methods.